On the factors affecting satisfaction and intention to stay of private teachers: A chi-square test approach - Melbert Hungo; Leomarich Casinillo; Ronel Dagohoy; Eduardo Lleve JR (Universidade Estadual de Alagoas, 2024)
Job satisfaction is a very crucial correlate for a teacher to stay in their current teaching assignment. This study looks into the significant factors of job satisfaction and intention to stay of teachers in a private school. In addition, the study also aims to investigate the relationship between job satisfaction and intention to stay of private teachers. Using a complete enumeration process, 34 private teachers were interviewed and primary data were collected from them. Necessary statistical measures were employed to describe the data collected and the Chi-square test for association was used to determine the relationship between the factors of satisfaction and intention to stay. Results indicated that most of the private teachers are just moderately satisfied with their current job and about 55.88% of them are not willing to stay in their job. This implies that working in a private institution is challenging and does not have enough economic security. This Chi-square test revealed that job satisfaction of private teachers is influenced by their civil status (p-value=0.100) and employment status (p-value=0.100). Additionally, the factors that influence their willingness to stay are their age (p-value=0.100) and employment status (p-value=0.052). The study suggests that teachers must be given incentives and the right compensation to increase their satisfaction and intention to stay in a private school.